(untitled) (Journal of Humanities and Social Sciences Research, 2023)
This paper covers the birth of the new shape of racism against Asian Americans in general and Chinese Americans in the particular century before the epidemic of the Coronavirus and after it. The paper reveals vividly how the Chinese in America faced the most malicious and pernicious kind of racial discrimination at the beginning of the 20th century and after the outbreak of Covid-19 in 2020, as reflected in Kati Lu’s Pandemic. She shows how the American government and the important politicians encouraged directly and indirectly the crimes of hatred and xenophobia using the antagonistic political discourse against China when the U.S. former President Donald Trump took advantage of the coronavirus crisis to revive and rage theories of conspiracy, white supremacy, anti-immigrant, extreme nationalism and against foreigners. Using the critical race theory (C.R.T.), the paper holds deep theoretical analyses of the conversations on the radio of Kati Lu’s Pandemic to prove that racism in America is ever-lasting. It is an irremediable disease after the Pandemic. That history revises itself as the actions of the play move between two different periods but struggles with the same problem, suffering, and policy. The second thing that has been proven in this research is that racism in America emerged from the concealment and secrecy that characterised it before the Pandemic to reveal its teeth to the stage of open, shameless, frank, tyrannical against other ethnic minorities, especially Asians.